2018
DOI: 10.5897/ijeaps2016.0457
|View full text |Cite
|
Sign up to set email alerts
|

Educational policies and programmes implementations: A case study of education funding, universal basic education (UBE) and teacher education

Abstract: The present state of the Nigeria education system brings worry to the hearts of all stakeholders because education goals such as producing skilled and professionally competent graduates, basic education for all, education for technological advancement, all to fulfil the dream of national development and prosperity, are yet farfetched from being a reality. Literatures were reviewed on three of the policies in education, which include: education funding, universal basic education and teachers' education for bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In the process of schools transitioning from traditional teaching models to digital education, the rational use and allocation of educational funds is crucial. Osarenren-Osaghae & Ibor (2018) pointed out that education funds can be used for equipment procurement, software development, teacher training, and educational research, all of which play a key role in promoting digital education [1] . Their research suggests that policy makers should prioritize investment in education funds to ensure that schools can fully utilize digital technology to improve education quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the process of schools transitioning from traditional teaching models to digital education, the rational use and allocation of educational funds is crucial. Osarenren-Osaghae & Ibor (2018) pointed out that education funds can be used for equipment procurement, software development, teacher training, and educational research, all of which play a key role in promoting digital education [1] . Their research suggests that policy makers should prioritize investment in education funds to ensure that schools can fully utilize digital technology to improve education quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly , Osaghae and Irabor, in their study about Nigerian schools found that schools lack funds to capacitate teachers to support child-headed households. 28 This argument is advanced by Engelbrecht, et al, who mentioned that there is limited financial support from the Department of Education. 29 Moreover, for effective interventions, there should be financial resources for the schools.…”
Section: Limited Resourcesmentioning
confidence: 99%
“…The implementation of educational policies is expected to lead to the desired outcomes that such policies seek to address. However, it appears that the implementation of educational policies does not always lead to the expected results (Osarenren-Osaghae & Irabor, 2018; Oyedeji, 2015). The literature suggests that poor policymaking processes and implementation may lead to a decline in the quality of education in a country (Osarenren-Osaghae & Irabor, 2018).…”
Section: Background To the Studymentioning
confidence: 99%
“…However, it appears that the implementation of educational policies does not always lead to the expected results (Osarenren-Osaghae & Irabor, 2018; Oyedeji, 2015). The literature suggests that poor policymaking processes and implementation may lead to a decline in the quality of education in a country (Osarenren-Osaghae & Irabor, 2018). Some researchers have also identified lapses in the policy formulation process in education.…”
Section: Background To the Studymentioning
confidence: 99%
See 1 more Smart Citation